Consideration of estimated energy requirements in Paralympic athletes - Motonaga, K. (Journal of High Performance Sport, 2020)
Estimating energy requirements is important in developing an athlete's nutrition plan. However, it may not be appropriate to calculate energy requirements for Paralympic athletes, or even people with disability by substituting the prediction equation of the non-disabled person as it is from the physical characteristics. Therefore, the aim of the study was to review methods of estimating energy requirements of Paralympic athletes which has been used in practice. The point of the estimation of the energy requirements is considered to estimate basal metabolic rates and to set physical activity levels. The evidence is currently confirmed in amputees, spinal cord-injured persons, and those with cerebral palsy. There have not yet been enough studies on athletes with other physical disabilities such as brain injury. For amputees, the method of estimating the basal metabolic rate by supplementing the lost limbs is used. The method is based on the concept of rehabilitation nutrition. For spinal cord-injured persons, it is known that the amount of basal metabolic rates depends on the damaged levels of the spinal cord. Among the persons with cerebral palsy, some can walk and the others use wheelchairs. The method of estimating the basal metabolic rates is considered by their movements. Therefore, there have much evidence to support that it is currently available to actually measure basal metabolic rates in Paralympic athletes. In the future, it will be necessary to collect evidence and contribute to the body of knowledge to estimate the energy requirements for Paralympic athletes.